Changing Epstein-Barr viral ZEBRA protein into a more powerful activator enhances its capacity to disrupt latency. - Baumann, R (1993)
The Epstein-Barr viral transcriptional activator ZEBRA induces expression of viral early lytic genes when introduced into cells bearing latent Epstein-Barr virus. We show here that a ZEBRA-herpes simplex viral protein 16 (VP16) fusion protein induces early viral lytic gene expression in Epstein-Barr virus-containing cells more efficiently than does wild-type ZEBRA. The fusion protein is also a more powerful transcriptional activator in these cells, as assayed with reporter constructs. Our experiments also suggest that ZEBRA manifests a function required for full activity on certain natural promoters but not on promoters bearing oligomerized ZEBRA binding sites; this function cannot be provided by VP16.